Epidemiology of genital warts in England and Wales: 1971 to 1994. Issue 5 (October 1997) - Simms, I; Fairley, C K
Abstract : OBJECTIVE: To describe the epidemiology of genital warts in England and Wales over the period 1971 to 1994. METHOD: Retrospective study of available statistics. RESULTS: The rate of attendance for genital warts increased by 390% and 594% for men and women respectively between 1971 and 1994. Most of this increase occurred between 1980 and 1986. From 1986 to 1991 virtually no change occurred, but since 1992 the rate of attendance has risen by 15%. The ratio of male to female cases has declined steadily from 1.85 in 1971 to 1.34 in 1994. Rates of attendance for first attack in men were highest in the 20 to 24 year age group whereas for women it peaked in those aged 16 to 24 years. Regional data indicate that the rate of attendance has increased consistently over England and Wales during this period. CONCLUSIONS: Rates of genital warts have risen substantially over the past 25 years. If these are a reflection of changes in sexual behaviour then the rise since 1992 is of considerable concern particularly for the incidence of cervical cancer in the coming decades.